(508) An Optimal Policy for Machine Tool Replacement سياسة مثلى لاستبدال أدوات الماكينات - A. Taha, Hamdy (INP, 2024)
This paper introduces a novel optimal policy for machine tool replacement, based on the premise that the number of defective items produced increases as the tool is used longer due to malfunctions. Conversely, frequent maintenance or corrective actions are expected to reduce the number of defective items. The goal is to determine the optimal time interval before maintenance or corrective actions should be performed, balancing the conflicting costs of tool maintenance and the reworking or scrapping of defective items. Two types of maintenance actions are considered: (1) replacement and (2) sharpening or adjustment. The model assumes that either maintenance action restores the tool to its original condition and that these actions are applied at evenly spaced intervals, as determined by optimal results. The type of maintenance action to be applied can be decided based on either a deterministic or probabilistic approach. Additionally, the paper proposes an approximation method for solving the integral equation that determines the optimal value of the decision variable in this context.